KOMUNIKASI PENYULUHAN DINAS PENGENDALIAN PENDUDUK DAN KELUARGA BERENCANA (KB) DALAM MENGGIATKAN FUNHSI REPRODUKSI PADA PENGUATAN KELUARGA DI KAMPUNG KB KELURAHAN BUKIT TIMAH KOTA DUMAI - Yasfianti, Hesty; Awza, Rusmadi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Kampung KB is a unit of area equivalent to Rukun Warga, hamlet or equivalent, which has certain criteria, where there is integration of population program, family planning, family development and related sector development systemically and systematically implemented. One of the cities appointed for the development of Kampung KB program in Riau is Dumai City. Government of Dumai City is committed to improve the health and social welfare of the community in realizing quality families, one of the efforts is made by promoting Kampung KB in a number of villages and sub-districts. The purpose of this research is to know the process of disseminating information of reproduction function, what method used in counseling, and what obstacle are felt.This research used qualitative research method. the subjects of the study consisted of 9 persons selected by using purposive techniques which is determined based on criteria of informan. Data collection techniques through observation, interviews, and documentation. To achieve the validity of data in this study the authors use the extension of participation and triangulation.The results of this study indicate that the process of disseminating information is by implementing counseling.First, before conducting counseling, communicators are selected by decree. The extension messages are informative and persuasive in accordance with the terms and guidelines. Media and communicant has been determined and determined by BKKBN. Second, the method used is individual approach and group approach.Third, while the obstacles that are felt during the counseling process include time constraints, the belief that many children a lot of sustenance, and low educational backgrounds inhibit the understanding of society.Keyword : Counseling, Kampung KB, disseminating information